2011
DOI: 10.1242/jeb.056010
|View full text |Cite
|
Sign up to set email alerts
|

Low metabolism in a tropical bat from lowland Panama measured using heart rate telemetry: an unexpected life in the slow lane

Abstract: SUMMARYAnimals must optimize their daily energy budgets, particularly if energy expenditures are as high as they are in flying animals. However, energy budgets of free-ranging tropical animals are poorly known. Newly miniaturized heart rate transmitters enabled this to be addressed this in the small, energetically limited, neotropical bat Molossus molossus. High-resolution 48 h energy budgets showed that this species significantly lowers its metabolism on a daily basis, even though ambient temperatures remain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 59 publications
1
52
0
Order By: Relevance
“…Here, we show that regardless of torpor bout length there is a strong correlation between f H and V · O 2 across a complete torpor bout and at rest, consistent with the potential for the f H method to reliably measure field energy expenditure. Although it has been suggested in the past that the f H method becomes prohibitively expensive when applied to animals smaller than 1 kg (Butler et al, 2004), miniaturised heart rate transmitters are becoming more readily available and can be used on animals as small as 10 g (Dechmann et al, 2011). Our study highlights the need for validation of this method for small heterothermic animals as torpor plays an important role in energy budgets for these animals and extrapolations from resting values are grossly inaccurate.…”
Section: Research Articlementioning
confidence: 91%
See 1 more Smart Citation
“…Here, we show that regardless of torpor bout length there is a strong correlation between f H and V · O 2 across a complete torpor bout and at rest, consistent with the potential for the f H method to reliably measure field energy expenditure. Although it has been suggested in the past that the f H method becomes prohibitively expensive when applied to animals smaller than 1 kg (Butler et al, 2004), miniaturised heart rate transmitters are becoming more readily available and can be used on animals as small as 10 g (Dechmann et al, 2011). Our study highlights the need for validation of this method for small heterothermic animals as torpor plays an important role in energy budgets for these animals and extrapolations from resting values are grossly inaccurate.…”
Section: Research Articlementioning
confidence: 91%
“…Unfortunately, current data are mainly limited to large homeothermic mammals and birds. However, in recent years technological advancements have led to the development of small, lightweight devices for f H telemetry, making measurements of f H in small animals feasible (Dechmann et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, because bats are inactive during the warmer daytime, their requirements for non-activityassociated thermogenesis are likely to be more modest than those for nocturnally inactive taxa [although the very short daily foraging periods of some bats (e.g. Dechmann et al, 2011) raise the possibility that this might not always be the case]. Conversely, resting heat production capacity in rodents is correlated with torpor use, with ME negatively correlated with both minimum air temperature and torpid T b (Careau, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In temperate latitudes with long, cold winters, many non-migratory bats hibernate for much of the year, usually in thermally stable hibernacula such as caves (Park et al, 2000;Ransome, 1990). Several tropical and subtropical species are also known to hibernate and/or use daily torpor under natural conditions in winter, and in some cases summer (Coburn et al, 1996;Cory Toussaint et al, 2010;Dechmann et al, 2011;Liu et al, 2011;Stawski et al, 2010;Turbill et al, 2003).…”
mentioning
confidence: 99%
“…A number of bat species in subtropical Australia are highly heterothermic (Stawski et al, 2010;Turbill et al, 2008;Turbill et al, 2003), and recent work in tropical central America has revealed that Molossus molossus maintains an almost continuous hypometabolic state (Dechmann et al, 2011). In subtropical Taiwan,…”
mentioning
confidence: 99%